Festivals of kiselo mlyako – a culinary tourism offer from Bulgaria to Europe and the rest of the world (Geography and Tourism, 2017)
Festivals of certain foods in Bulgaria are a good initiative to promote the country to foreigners. This is a good and inexpensive way to show traditional Bulgarian food. The accompanied culinary geography and holidays became very important in the life of every Bulgarian. This paper will clarify the origin of kiselo mlyako, its distribution, consumption per capita, useful properties and influence on the human body. We will describe where the festivals of the product are organised and how they can be attended. The development of culinary tourism and festivals in these parts of the country will contribute to better and faster economic development in this area.